Responsabilidade civil na arbitragem - Bimonti, Helena (2018)
The concept of arbitration has been constructed, over time, as a legitimate and alternative instrument to the Brazilian Judiciary, serving to solve several kind of conflicts. Obviously none of that would have been possible without the arbiter’s performance, who is the most important figure in the procedure, and, given their essentiality, has specifics duties and qualities. These duties and qualities do not always come free of questions, which is why they will be analyzed in this study. Moreover, considering the fact that arbitration presents, as a guiding principle, the freedom of will of the parties, who must be aware of everything, there’s another question to be answered, equally important: working on the premise that all acts are practiced under the agreement of the parties, could any liability be applied to the arbiters, when exercising their judging function? Also, could the arbitrational agency, which usually manages the activities in the procedure, be responsible for anything as well? This is the purpose of this study, which aims first to approach the scope of the duties conferred to the arbiters and to the arbitrational agencies, and then the possibility of their civil liability